EFFECTIVENESS OF INTERVAL EXERCISE VERSUS CONTINUOUS EXERCISE TO IMPROVE EXERCISE TOLERANCE IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE SUBJECTS (International Journal of Physiotherapy, 2015)
Background: COPD is characterized by chronic airflow limitation and a range of pathological changes in the lung. Chronic inflammation causes structural changes and narrowing of the small airways and destruction of lung parenchyma, leads to the loss of alveolar attachments to the small airways and decreases lung elastic recoil; in turn these changes diminish the expiration and the work of breathing is increased. Scarcity of evidence on continuous and interval exercises is forcing researchers conduct studies on effectiveness of interval exercise with continuous exercise on exercise tolerance in subjects with COPD.Methods: 60 subjects were selected by lottery method. All the subjects were explained about the condition and mode of assessment and written informed consent were obtained from them and divided into 2 groups interval training group and continuous exercise training group and subjects were scheduled to attend exercise session 5 days a week for 4 weeks with exercise duration 20 min’s with cycle ergometer. Outcome measure: six minute walk test and heart rate.Results: On observing the means of post test parameters of experimental group A and experimental group B Independent t-test was done and the P- value is >0.05 .It shows a no significant difference between the two groups.Conclusion: The results had shown that both interval exercise group and continuous exercise group who received four weeks of therapy has improved significantly on pre and post test values within the groups but when compared between these groups there is no statistical significance noted. So this study concluded that there is no significant difference between interval exercise group and continuous exercise group in improving exercise tolerance among COPD subjects.